2005
DOI: 10.1080/01674820500168350
|View full text |Cite
|
Sign up to set email alerts
|

Vestibulodynia (former vulvar vestibulitis): Personality in affected women

Abstract: The present results indicate the importance of identifying psychological factors in order to optimize the care of vestibulodynia patients and to relieve their symptoms and improve their situation. We therefore want to emphasize that vestibulodynia patients should always, in addition to medical examination and treatment, also be psychologically examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
4
14
0
2
Order By: Relevance
“…Women's sexual distress was assessed using the Female Sexual Distress Scale (FSDS) and partner' sexual distress was measured using an adapted version of this scale. The scale consists of 12 items assesing sexual distress over the previous month to which participants answered on a 5-point Likert-type scale ranging from never (0) to always (4). For partners, the adapted version consisted of 8 items identical to those of the FSDS and 4 adapted items targeting the sexual distress related to the woman's sexual problem.…”
Section: Main Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Women's sexual distress was assessed using the Female Sexual Distress Scale (FSDS) and partner' sexual distress was measured using an adapted version of this scale. The scale consists of 12 items assesing sexual distress over the previous month to which participants answered on a 5-point Likert-type scale ranging from never (0) to always (4). For partners, the adapted version consisted of 8 items identical to those of the FSDS and 4 adapted items targeting the sexual distress related to the woman's sexual problem.…”
Section: Main Outcome Measuresmentioning
confidence: 99%
“…It is often characterized by a recurrent and burning pain upon pressure to the vestibule, such as during vaginal penetration or tampon insertion [2]. This persistent pain affects women and their partners' wellbeing, and women report significantly lower sexual satisfaction and more sexual and psychological distress compared to women without PVD [3][4][5][6][7][8][9]. The fact that this condition is often misdiagnosed or ignored may partly explain women's distress.…”
Section: Introductionmentioning
confidence: 99%
“…Green and Hetherton (2005) carried out a systematic review of publications on the psychological aspects of vestibulitis (now vestibulodynia). They concluded that there was marked inconsistency between studies, with those carried out in a specialist setting tending to show greater levels of psychological morbidity (anxiety and depression) than controls (Stewart et al 1994, Masheb et al 2002, Wylie et al 2004, Lundqvist & Bergdahl 2005, Latthe et al 2006, while community surveys tended not to show such differences. The authors suggested that confounding factors involved in the process of referral to specialist services might play a part as there would be selection bias, many of these patients having a worse psychological profile as well as more severe physical symptoms.…”
Section: Chronic Vulval Pain Syndromesmentioning
confidence: 99%
“…As with sexual dysfunction, clinicians should acknowledge that depression occurs frequently in women with VVS, as with other pain syndromes [37][38][39][40][41].…”
Section: Depressionmentioning
confidence: 99%